Distance Learning through the Grand Egyptian Museum: Leveraging Modern Technology to Teach about Ancient Egypt among Schools and National Museums - Nevine Nizar Zakaria (MDPI AG, 2024)
By considering the increasing emphasis on lifelong learning and the ongoing significant debates over the value and utility of digital technologies in accelerating long-established learning tasks, the paper suggests new approaches for the national museums of Egypt to incorporate distance learning and museum-based online programs as a means to improve their traditional educational programs. This would significantly help school students better understand the ancient history of Egypt, "Pharaonic Egypt", which is an essential part of their formal school curriculum. Moreover, it provides much-needed support to museums with limited or insufficient educational programs to promote more meaningful learning experiences. The proposed approach can be effectively implemented through the Grand Egyptian Museum (GEM), the world's largest archaeological museum complex dedicated to the culture of ancient Egyptian Pharaonic Culture. The study discusses the GEM's educational and digital infrastructure capabilities in creating a robust online learning platform that provides access to rich educational content and digital resources across Egypt's various geographic regions, enhancing museum education concerning pharaonic Egypt in line with the state's cultural policy to strengthen national identity among future generations. By analyzing both qualitative and quantitative data, the study investigates the potential benefits of integrating online digital technologies into the pedagogical and educational practices of Egypt's national museums. It concludes by providing practical recommendations for future research and actions encouraging online learning among Egyptian museums, aligned with recent national efforts toward Egypt's digital transformation.